Triaging psychiatric care: risk assessment construction and validation for washington’s involuntary treatment and forensic commitment populations - Kigerl, Alex (International journal of offender therapy and comparative criminology, 2017)
There is a growing need in Washington to triage patients being considered for inpatient treatment. There has previously been no risk assessment normed to persons with mental illness in the State of Washington. The Static Risk Assessment (SRA) is used in Washington to assess risk among offenders under State Department of Corrections supervision. The present study sought to create and validate a new risk assessment, the SRA for Mental Health Patients (SRA-MHP), for two mental health populations in Washington. A sample of 16,289 patients involuntarily committed due to being deemed dangerous or gravely disabled, as well as a sample of 8,713 forensic patients undergoing a competency evaluation to stand trial after being charged with a crime, was gathered to assess the utility in applying the SRA-MHP to persons with mental illness. Results indicate that the SRA-MHP has high predictive performance for these samples.